Early Transylvanian Antitrinitarianism (1566-1571): From Servet to Paleologus - Balázs, Mihaly (Verlag Valentin Koerner GmbH, 1996)
Monographical study of special religious dissidents of the 16th and 17th centuries. Here: Early Transylvanian Antitrinitarianism. Two regions of Central Eastern Europe, Poland and Transylvania, played important roles in the history of sixteenth and seventeenth century Antitrinitarianism. Developements in Poland are much better known to scholars. This study is endeavouring to answer why Transylvania became a center of such dogmatic radicalism, and whether Trasylvanian Antitrinitarism of the 1560s displayed peculiarities that could explain this phenomenon.